Hole Hopping Across a Protein-Protein Interface - Takematsu, Kana; Pospíšil, Petr; Pižl, Martin; Towrie, Michael; Heyda, Jan; Záliš, Stanislav; Kaiser, Jens T; Winkler, Jay R; Gray, Harry B; Vlček, Antonín (The journal of physical chemistry. B, 2019)
We have investigated photoinduced hole hopping in a Pseudomonas aeruginosa azurin mutant Re126WWCu , where two adjacent tryptophan residues (W124 and W122) are inserted between the Cu center and a Re photosensitizer coordinated to a H126 imidazole (Re = Re (H126)(CO) (dmp) , dmp = 4,7-dimethyl-1,10-phenanthroline). Optical excitation of this mutant in aqueous media (≤40 μM) triggers 70 ns electron transport over 23 Å, yielding a long-lived (120 μs) Re (H126)(CO) (dmp )WWCu product. The Re126FWCu mutant (F124, W122) is not redox-active under these conditions. Upon increasing the concentration to 0.2-2 mM, Re126WWCu and Re126FWCu are formed with the dmp ligand of the Re photooxidant of one molecule in close contact (3.8 Å) with the W122' indole on the neighboring chain. In addition, Re126WWCu contains an interfacial tryptophan quadruplex of four indoles (3.3-3.7 Å apart). In both mutants, dimerization opens an intermolecular W122' → //*Re ET channel (// denotes the protein interface, *Re is the optically excited sensitizer). Excited-state relaxation and ET occur together in two steps (time constants of ∼600 ps and ∼8 ns) that lead to a charge-separated state containing a Re(H126)(CO) (dmp )//(W122 )' unit; then (Cu )' is oxidized intramolecularly (60-90 ns) by (W122 )', forming Re (H126)(CO) (dmp )WWCu //(Cu )'. The photocycle is closed by ∼1.6 μs Re (H126)(CO) (dmp ) → //(Cu )' back ET that occurs over 12 Å, in contrast to the 23 Å, 120 μs step in Re126WWCu . Importantly, dimerization makes Re126FWCu photoreactive and, as in the case of Re126WWCu , channels the photoproduced "hole" to the molecule that was not initially photoexcited, thereby shortening the lifetime of Re (H126)(CO) (dmp )//Cu . Although two adjacent W124 and W122 indoles dramatically enhance Cu → *Re intramolecular multistep ET, the tryptophan quadruplex in Re126WWCu does not accelerate intermolecular electron transport; instead, it acts as a hole storage and crossover unit between inter- and intramolecular ET pathways. Irradiation of Re126WWCu or Re126FWCu also triggers intermolecular W122' → //*Re ET, and the Re(H126)(CO) (dmp )//(W122 )' charge-separated state decays to the ground state by ∼50 ns Re (H126)(CO) (dmp ) → //(W122 )' intermolecular charge recombination. Our findings shed light on the factors that control interfacial hole/electron hopping in protein complexes and on the role of aromatic amino acids in accelerating long-range electron transport.